The flying hill profile as a limitation factor in development of world record in ski flying - Jošt, B.; Vodicar, J. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Flying Hill in 2011 by Johan Reemen Evensen of Norway. In 2014 ski flying hills of the same size, i.e. HS225, were constructed in Kulm and Planica. The aim of this paper is to study the possibility of a new world record being set at the newly-reconstructed Planica hill. The study uses the flight curves determined from the kinematic properties of flights performed at the Planica World Cup Ski Flying competitions (2008/2009 and 2012/2013 seasons) and the 2010 Ski Flying World Championship.